2014
DOI: 10.4049/jimmunol.1301707
|View full text |Cite
|
Sign up to set email alerts
|

Th1 Polarization of T Cells Injected into the Cerebrospinal Fluid Induces Brain Immunosurveillance

Abstract: Although CD4 T cells reside within the cerebrospinal fluid, it is yet unclear whether and how they enter the brain parenchyma and migrate to target specific Ags. We examined the ability of Th1, Th2, and Th17 CD4 T cells injected intracerebroventricularly to migrate from the lateral ventricles into the brain parenchyma in mice. We show that primarily Th1 cells cross the ependymal layer of the ventricle and migrate within the brain parenchyma by stimulating an IFN-γ–dependent dialogue with neural cells, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Depletion of regulatory T (Treg) cells in an AD mouse model accelerated the onset of cognitive deficits without altering brain Aβ load (Dansokho et al , 2016). Administration of Aβ-specific type 1 T helper (Th1) cells into the brain lateral ventricle of an AD mouse model enhanced removal of cerebral Aβ deposits and promoted neurogenesis without harmful effects (Fisher et al , 2014). Thus, these T cells play beneficial roles in the AD pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of regulatory T (Treg) cells in an AD mouse model accelerated the onset of cognitive deficits without altering brain Aβ load (Dansokho et al , 2016). Administration of Aβ-specific type 1 T helper (Th1) cells into the brain lateral ventricle of an AD mouse model enhanced removal of cerebral Aβ deposits and promoted neurogenesis without harmful effects (Fisher et al , 2014). Thus, these T cells play beneficial roles in the AD pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are huge discrepancies with respect to cytokine production from Th1 or Th2 cells and the ratio of Th1/Th2 cells can even affect stroke severity . Th17 cells and γδ T cells produce pro‐inflammatory cytokines and chemokines, usually impairing neurogenesis . However, it is recently suggested that IL‐17A secreted by γδ T cells unexpectedly promoted neuronal differentiation via p38 mitogen‐activated protein kinase in cultured NPCs .…”
Section: The Role Of Neuroinflammation In Multiple Brain Repair Mechamentioning
confidence: 99%
“…In the same mouse model of AD, Aβ-specific Th1 cells were intracerebroventricularly injected into the Cerebrial spinal fluid of APP/PS1 mice, and showed to target Aβ plaques that resulted in reduction of Aβ plaque load and slight enhancement of neurogenesis [54]. This dichotomous role of Th1 cells in Alzheimer's Disease indicates that the route of migration (localization) and temporal factors may play a role in whether antigen-specific Th1 cells are beneficial or detrimental in neuro-degeneration.…”
Section: T Cell Subsets and Consensual Roles In Neural De/re-generatimentioning
confidence: 99%